Combination of Focused Ultrasound, Immunotherapy, and Chemotherapy: New Perspectives in Breast Cancer Therapy. (23rd July 2022) - Dahan, Myléva; Cortet, Marion; Lafon, Cyril; Padilla, Frédéric
Abstract : Focused ultrasound is a treatment modality increasingly used for diverse therapeutic applications, and currently approved for several indications, including prostate cancers and uterine fibroids. But what about breast cancer? Breast cancer is the most common and deadliest cancer in women worldwide. While there are different treatment strategies available, there is a need for development of more effective and personalized modalities, with fewer side effects. Therapeutic ultrasound is such an option, and this review summarizes the state of the art in their use for the treatment of breast cancer and evaluate potentials of novel treatment approaches combining therapeutic ultrasound, immuno‐ and chemo‐therapies.